Phenotypic plasticity in Toggenburg dairy goats on milk production traits across agro-ecological zone of South Africa - Matshebuka, Tshepho (My University, 2025)
Toggenburg dairy goats, which are valued for their versatility and excellent milk production under a variety of environmental conditions, are essential to the South African dairy industry. The aim of this study was to evaluate the phenotypic plasticity of the Toggenburg goat breed in milk production in South Africa's various agroecological zones (AEZ). Performance records of 2417 does born from 1955-2018 across five agro-ecological zones with five differing breed purity levels were obtained from the Milch Breeders Society of South Africa LOGIX database. Pedigree data and reproductive indices were included with the performance data. Descriptive statistics of milk production, reproductive, and dairy value traits computed using General Linear Model of Minitab 18.1 software. Significant animal and environmental factors affecting productivity were determined using ANOVA. Four methods of determining the phenotypic plasticity index (PPI) were compared. These were reaction norm-based, infinite-dimensional model, character trait, and variance-based model. The p-value and R2 values were used to assess the significance of the estimates and goodness-of-fit. Data visualisation techniques used included surface plots and phenotypic plasticity trends. The results showed that the winter kidding season showed high kid status (0.6269±0.0820 healthy) (p<0.05), while spring showed the highest somatic cell count (SCC) (302±103 cells/ml). AEZs significantly (p<0.05) influenced the arid zone to produce the largest litter size (2.069±0.113 kids) and the temperate zone produced the highest lactation milk yield (647.32±5.59 kg). Blood breed purity levels showed a significant effect (p<0.05), with a high lactation milk yield in Founders (675.1±17.9 kg). Litter size was affected by dam parity (p<0.05), with a higher number of kids at parities 2 (1.9464±0.0984 %), 3 (1.947±0.100 %), 4 (2.052±0.108 %), 5 (1.958±0.115 %), and 7 (2.183±0.164 %). At parity 10 better milk persistency (81.54±8.18 %) was observed. Variance-based and character trait methods revealed significant phenotypic plasticity (p<0.05) in somatic cell count, kid status score, litter size, and ease score in high humidity and low temperature zone. Reaction norm analysis also demonstrated significant plasticity (p<0.05) in kid status score, birth difficulty score, Milk Urea Nitrogen, milk persistency, lactation value index, lactose with R² of 81.58% milk yield exhibiting a high R² of 99.64% among the F0 purity levels. Regression model analysis confirmed significant (p<0.05) genotype-by-environment (GxE) interactions (p<0.05) for lactose with R² of 81.58%, dam longevity (r = 82.57%), milk persistence, birth difficulty score, and kidding ease score. PPI was not significant (p>0.05) across genotypes and AEZ in key AFK and KI in all methods. Surface plots and phenotypic plasticity trends confirmed the observed results in all traits, with lactation milk yield, prolificacy (litter size), and dam longevity indicating conspicuous phenotypic plasticity. The study concludes that the evaluated fixed factors have a significant impact on Toggenburg goat reproductive performance, milk production traits, and dairy value traits. Therefore, Toggenburg goat blood purity levels exhibit phenotypic plasticity, showing their ability to adapt to changing environmental conditions in the various agro-ecological zones of South Africa, revealing the reaction norm-based method as the most effective for assessing phenotypic plasticity.
Thesis (M. Sc. Agriculture (Animal Production)) -- University of Limpopo, 2025
Keywords: Studbook; Dairy value traits; Breed purity levels; Persistency; Dam longevity; Goats; Goat milk; Goats -- Milk yield